HUBUNGAN PENGETAHUAN DAN SIKAP PERAWAT TERHADAP PENERAPAN PASIENT SAFETY DI RUANG RAWAT INAP RSUD H.M ANWAR MAKKATUTU BANTENG - Tn Zainuddin (Voice of Midwifery, 2018)
The incidence of 28.3% of patient safety violations done by nurses. Nurses should be aware of its role as the safety of patients in hospitals and should be able to participate actively in realizing well. Hard working nurses can not reach optimal if it is not supported by the infrastructure, the management of hospitals and other health personnel. This study aims to determine the relationship of knowledge and attitude of nurses in the application of patient safety in the inpatient hospital H.M Anwar Makkatutu Bantaeng. This research used analytic survey with cross sectional study. The population was all nurses in the inpatient unit with 66 respondents. Sampling technique used purposive sampling with total sample of 57 respondents. Data were processed using univariate and bivariate analysis. The independent variable is the knowledge and attitude of nurses, the dependent variable is the application of patient safety by using chi square test. The results showed that the relationship of knowledge and attitude of  ρ= 0,000 nurses in the application of patient safety with the value  Based on these results we can conclude that there is a relationship between knowledge and attitude of nurses in the application of patient safety in the inpatient hospital H.M Anwar Makkatutu Bantaeng. Keywords : knowledge, attitude, application of patient safety